Th. L. Papadopoulos & E. Papadopoulou–Chrysikopoulou. Excavations at the Mycenaean Cemetery at Aigion – 1967 / K. Aktypi. The Mycenaean Cemetery at Ayios Vasileios, Chalandritsa, in Achaea - Dickinson, Oliver (Journal of Greek Archaeology, 2018)
These are two publications of material from Mycenaean chamber tombs excavated in rescue work in Achaean cemeteries, both at potentially important sites, but one considerably better documented than the other. The tombs at Aigion, an east Achaean coastal site with a long history that was probably the most prominent settlement of its region, are four of a larger cemetery (at least 15 tombs are known), which were excavated by the late E. Mastrokostas while ephor.